(untitled) (Annals of Medical Research, 2022)
Aim: Androgens are hormones that are essential for the differentiation and development of male genital organs, preserving their structural features and maintaining their functions. These hormones exert their effects on target tissues mainly through androgen receptors (AR). The aim of this study was to determine the AR immunoexpression pattern in the genital tissues of male mice. Materials and Methods: A total of 6 BALB/c male mice were anesthetized with ether, and the genital tissues, which were quickly removed from the body, were fixed in Bouin’s solution for 18 hours. Tissues that underwent routine histological procedures after fixation were embedded in paraffin. Tissue sections cut with a thickness of 5 µm from paraffin blocks were taken on a slide and examined by staining with immunohistochemical methods. Results: AR-positive immunostaining in the testis was observed only in somatic cells such as Sertoli, peritubular myoid cells, and Leydig cells. Germ cells were AR-negative. In the caput epididymis, ductus deferens, and seminal vesicle, AR positive immunoexpression was observed in stromal cells, especially epithelial cells. Although AR-positive staining was observed in some of the epithelial and stromal cells in these organs, some of them were AR-negative. Conclusion: In the current study, it was determined that the AR expression pattern in the genital tissues of male BALB/c mice was similar to that in other species, although there were minor differences. The findings support the hypothesis that androgens exert their effects in testis mainly through somatic cells, and their effects in other genital tissues through epithelial cells, and the fact that androgens/ARs are essential for maintaining the structures and functions of male genital organs.